Relações de gênero e sexualidade na escola Maria Antonieta de Paiva: práticas pedagógicas das/os professoras/es da educação infantil - SOUZA, Alycelene Ferreira de (2021)
The present work deals with the Relations of gender and sexuality in the Maria Antonieta de Paiva school, in the sense of researching the pedagogical practices of the teachers of a kindergarten class in the city of Acará. This research aims to analyze the practices of teachers in the kind of teaching of Early Childhood Education and to verify whether the document Pedagogical Political Project addresses the theme of gender relations and sexuality in their writings. The research raises the following questions: How do teachers in the early childhood class work on gender and sexuality relations in the classroom? How can the Pedagogical Political Project be structured on this theme? It is a study based on the post-critical approach, whose focus is to emphasize the importance of including cultural, social and historical studies of gender and sexuality issues in the school context. The type of research selected for this work is discourse analysis, through observations in the classroom and also in the school environment related to interviews from the teachers' statements. To assist in this research, it was also necessary to collect information through the use of semi-structured interviews. As a theoretical basis to reinforce this research, I highlight the main authors such as Felipe (2006), Foucault (1969,1990,1992), Louro (1997), Paraíso (2004) Pereira (2015), Scott (1995) and among others who have influenced these cultural diversity of gender and sexuality from a post-critical perspective. The research portrays the cultural, social and historical processes of the concepts of construction of relations of gender, sexuality, childhood and early childhood education in Brazilian society together with the teaching action between students and teachers. As a result of the observations and interviews, it is also noted that the pedagogical practices are not widely articulated before the children, emphasizing the construction of gender and sexuality relations in the classroom.